Techno-economic assessment of biogas production from press mud in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2013)
To assess the potential of biogas generation, as a new and renewable source of energy, physico-chemical parameters of press mud have been determined. It has considerable amount of volatile matter (75-80%) and C/N ratio (13-15) is slightly lower than the normal requirement for biomethanation. The total gas yield was 0.18 L/g and it contained about 65% methane. Biogas generation was studied in a 150 cft plant in the field at solid concentrations of 6 to 8%. Acclimatization of the reactor has been done by initial start-up by cow dung and gradual mixing with press mud in order to generate biogas from press mud alone. The profitability of the considered plant has been assessed using the discounting and dynamic Net Present Value methods. The biogas and biofertilizer production from press mud was found to be economically feasible. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15414 Bangladesh J. Sci. Ind. Res. 48(1), 51-58, 2013